3 Outcomes following Primary Percutaneous Coronary Intervention in Patients with multi-vessel Coronary Artery Disease in the Modern Era. (6th June 2015) - Noman, Awsan; Edwards, Richard; Veerasamy, Murugapathy; Bagnall, Alan; Purcell, Ian; Zaman, Azfar; Stewart, Andrew; Hannah, Andrew; Alhous, Hafez
Abstract : Background: The optimal timing of non-culprit lesion PCI in ST elevation myocardial infarction (STEMI) patients with multi-vessel coronary artery disease (MVD) treated primary percutaneous coronary intervention (PPCI) remains uncertain. Aim: To assess early (<30 days) and late (30 day – 1 year) mortality and one-year emergency (non-planned) repeat PCI (rePCI) following PPCI, according to MVD status. Methods: After excluding patients with cardiogenic shock and those with previous CABG, a total of 3486 PPCI-treated STEMI at two tertiary centres were included in this study. Patients were divided into 3 groups according to their MVD status and the number of coronary arteries treated at time of PPCI: 1) single vessel disease (SVD, n = 2164); 2) culprit-only multi-vessel disease (CO-MVD, n = 790); and 3) multi-vessel PCI MVD disease (MVPCI-MVD, n = 193) group. Results: Patients in SVG group were younger and were less likely to have previous history diabetes mellitus, hypertension, previous MI or CVA proportion of females compared to other groups. Overall one year emergency rePCI rate was 2.9%. One year emergency rePCI was significantly higher in CO-MVD group (7.5%) compared to SVD group (1.4%) and MVPCI-MVD group (2.1%). Overall 30-day and late mortality rates were 3.7% and 3.2%, respectively. Compared to SVG, both multi-vessel groups were associated with increased 30-day mortality; with adjusted odds ratios (95% confidence interval [CI]) of 1.69 (1.11–2.57) in CO-MVD and 1.78 (0.92–3.43) in MVPCI-MVD group, but not with late mortality; with hazard ratios (95% CI) of 1.01 (0.65–1.56) in CO-MVD and 0.88 (0.42–1.86) in MVPCI-MVD. Overall 30-day and late emergency PCI rates were 1.2% and 1.7%, respectively. Compared to SVD group, Conclusions: In this large observational study of unselected PPCI-treated patients, MVD was associated with increased 30-day mortality but not with mortality beyond 30 days. Furthermore, rate of emergency repeat PCI was highest in CO-MVD compared to other groups.